Мелкие млекопитающие из палеолитических стоянок Крыма - Маркова, А.К. (Археологический альманах, 2009)
As a result of analysis of small mammal faunas from Kabazi II, Kabazi V, Starosele, Karabi Tamchin, Buran Kaya III, Chokurcha I and Siuren I Palaeolithic sites, we could distinguish the following principal features: 1. The cold-adapted species of small mammals (such as Siberian and collared lemming, East Siberian voles, Arctic shrew and others) were not distinguished in the cultural layers of all of the sites; 2. The open landscapes species are the dominant in the all of the faunas and include as well as mammals which are habituated in modern landscapes, so the animals which now are distributed far away eastward and northward from the Crimea (yellow steppe lemming, narrow-skull vole, bobac, thick-tailed three-toed jerboa, lesser five-toed jerboa and others) (Fig. 1). 3. The remnants of forest small mammals are rather scarce. They were found in the communities correlated with the Mikulino (=Eemian) Interglacial (Kabazi II, V, VI), in the faunas correlated with Hengelo Interstadial (Kabazi V, III/5; Starosele, 1, 2; Karabi Tamchin, III), Denekamp = Briansk Interstadial (Buran Kaya III, B; Siuren I, Ga; Kabazi V, II/4a-II/7, III/1 and III/1A) (Fig. 2). The presence of these mammals indicates the increasing of humidity during these intervals. However, the forest species undoubtedly didn’t disappear from the Crimean Mountains even during the stadial cooling and only decreased their ranges. 4. Some species of small mammals distinguished from Crimean sites now are distributed eastward: the yellow steppe lemming survived in the Zaisan Depression, Mongolia, China; the narrow skull vole distributed in open landscapes of northern-eastern part of Eastern Europe, in the Urals, in steppe and tundra zones of Siberia. The ranges of thick-tailed three-toed jerboa and lesser five-toed jerboa decreased and located now eastward from Crimea. The Russian mole rat range (the remains of this animal was found only in the Eemian layers of Kabazi II) now is absent in the Crimea fauna. Its modern range located in Eastern Europe northward from the Crimean Peninsula. The similar changes were happened with the position of bobac marmot range.